The SCF-type E3 Ubiquitin Ligases as Cancer Targets - Kitagawa, Kyoko; Kitagawa, Masatoshi (Current Cancer Drug Targets, 2016)
The ubiquitin system controls protein stability and function. F-box proteins form SCF (SKP1-Cullin1-F-box protein)-type ubiquitin (E3) ligases to selectively target their substrates for degradation via the ubiquitin–proteasome pathway. Here, we review F-box proteins associated with cancer development. S-phase kinase-associated protein 2 (SKP2) (also known as FBXL1) is often overexpressed in human cancers, and functions as an oncogenic E3 ligase to degrade tumor suppressor gene products. Moreover, F-box/WD repeat-containing protein 7 (FBXW7) (also known as Fbw7) is often mutated in human cancers and functions as a tumor suppressive E3 ligase targeting oncogenic proteins for degradation. SKP2 is a potential drug target for cancer therapy and FBXW7 is useful in determining patient diagnosis, prognosis, and drug sensitivity. In this review, we also discuss other F-box proteins involved in cancer-associated cellular processes such as cell cycle control, epigenetic regulation, epithelial mesenchymal transition, apoptosis/survival, drug resistance, and DNA-damage responses.
Keywords: E3 ligase